Inicjacje w najnowszej prozie wiejskich przestrzeni. Rekonesans - Czyżak, Agnieszka (Zagadnienia Rodzajów Literackich, 2022)
The main purpose of this article is to consider the problems associated with the theme of initiation and the Bildungsroman genre, particularly in the literary area known as the prose of rural spaces. New forms of initiatory perspective — an important part of fiction written in the last decade of the twentieth century — have been used by many authors as methods that enable them to present a vision of an individual and shared past (previously distorted by state censorship). In literature written since the beginning of the 21st century, these tendencies were also signs of new cultural phenomena of collective life. The debuts of Mirosław Nahacz or Dorota Masłowska are regarded as examples of expressing the widespread (at that point in history) disillusionment caused by the processes brought about by political transformation. The article then focuses on the relationship between the literature of peripheral spaces, individual biographical emotions, and new visions of shared history. Initiations in the prose of rural spaces are presented through examples of contemporary Polish literature written by older authors (Wiesław Myśliwski, Marian Pilot) and by young writers (e.g., Andrzej Muszyński, Ignacy Karpowicz, Wioletta Grzegorzewska, Weronika Gogola, Maciej Płaza, Anna Ciarkowska). Interpretative activities and reflections on genre lead to the recognition of a new form of relationship between literature and everyday life.